2021
DOI: 10.1101/2021.12.02.471004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Phylogenetics using Parsimony Produces Slightly Better Trees and is Dramatically More Efficient for Large SARS-CoV-2 Phylogenies than de novo and Maximum-Likelihood Approaches

Abstract: Phylogenetics has been foundational to SARS-CoV-2 research and public health policy, assisting in genomic surveillance, contact tracing, and assessing emergence and spread of new variants. However, phylogenetic analyses of SARS-CoV-2 have often relied on tools designed for de novo phylogenetic inference, in which all data are collected before any analysis is performed and the phylogeny is inferred once from scratch. SARS-CoV-2 datasets do not fit this mould. There are currently over 5 million sequenced SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…0.51% higher than the starting tree. This is consistent with our previous analyses ( Thornlow et al , 2021 ) in which we observed that parsimony and likelihood scores are strongly correlated for SARS-CoV-2 phylogenies. We also observed that in some cases, the PangoLEARN lineage assignments ( O’Toole et al , 2021 ) appeared a little less dispersed through the tree ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…0.51% higher than the starting tree. This is consistent with our previous analyses ( Thornlow et al , 2021 ) in which we observed that parsimony and likelihood scores are strongly correlated for SARS-CoV-2 phylogenies. We also observed that in some cases, the PangoLEARN lineage assignments ( O’Toole et al , 2021 ) appeared a little less dispersed through the tree ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, TNT incurs a long startup delay followed by a slow improvement of parsimony. matOptimize is therefore especially well-suited for SARS-CoV-2 online phylogenetics ( Thornlow et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UShER takes a starting tree, built with iqtree or a similar approach, and incrementally adds sequences by maximum parsimony. For densely sampled sequencing efforts, as in the SARS-CoV-2 pandemic, such an approach still yields tree topologies of very high quality ( Thornlow et al, 2022 ). To turn this distance tree into a time tree, by estimating a time associated with each node in the tree, we recently developed Chronumental ( Sanderson, 2021 ) which uses stochastic gradient descent to efficiently construct chronologies from very large trees, which was not possible with previous approaches.…”
Section: Introductionmentioning
confidence: 99%